STUDI ANALISIS PEMANFAATAN AIR GARAM SEBAGAI SUMBER ENERGI ALTERNATIF MENGGUNAKAN ELEKTRODA KARBON BATERAI BEKAS - Antonov Bachtiar; Yusreni YUSRENI WARMI Warmi; Zuriman Anthony; Aswir Premadi; Asnal Effendi; Dasman Dasman; Rahmat Fajri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This research is motivated by the current fact that the availability of energy sources on the earth continues to increase and the demand for energy continues to increase in line with the increasing demand for energy on earth. population growth. So the use of new renewable energy sources and environmentally sound is needed. This study aims to determine the voltage generated using used battery carbon electrodes and copper, the effect of used battery carbon electrodes and single copper wire on the resulting voltage and the effect of salt content on the resulting voltage capacity. From the research results, it is obtained that the carbon electrodes of used batteries and copper can generate voltage using a solution of salt water and sea water. The highest voltage in the salt water solution is 1965mV and the lowest voltage is 405mV. In seawater solution, the highest voltage is 2071mV and the lowest voltage is 1890mV. The effect of the electrode on the resulting voltage is whether or not the entire surface of the electrode is immersed so that it affects the resulting voltage. And the effect of salt content on the resulting stress is 10%, 5%, 3%, 2% and 37%. With successive voltages of 740mV, 1777mV, 1965mV, 1920mV and 2071mV. With this it can be concluded that the use of used battery carbon electrodes and single copper wire as a substitute for electrodes in generating voltage using an electrolyte solution of salt water and sea water can be used as an alternative energy source. Keywords: Salt Water, Alternative Energy, Used Carbon Electrodes, Copper Electrodes , Electrochemistry .